ANALISIS PENGARUH TRADING VOLUME ACTIVITY DAN DEBT MATURITY STRUCTURE TERHADAP STOCK PRICE CRASH RISK - Aurellia Berliana; R.A. Norromadani Yuniati; Arfiana Dewi (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2024)
The stock price conditions from 2018-2023 have always experienced fluctuations and crashed in 2020 due to the COVID-19 pandemic. This has made investors cautious when investing in stocks to avoid the risk of a stock price crash. This study aims to determine the effect of Trading Volume Activity and Debt Maturity Structure on Stock Price Crash Risk in transportation and logistics companies listed on the Indonesia Stock Exchange from 2018-2023. The sampling technique used in this study is purposive sampling, and a sample of 10 companies that meet the criteria from 37 companies was obtained. The type of data used is secondary data obtained from www.finance.yahoo.com. The analysis technique used in this study is Panel Data Regression. The results show that Trading Volume Activity does not affect Stock Price Crash Risk. And Debt Maturity Structure have a positive effect on Stock Price Crash Risk.